The 7th of October Occurrence, Palestine in Fullmetal Alchemist Anime Portrayal - Setiawan, Budi Rahmat (Research Community for Critical Society and Environment, 2024)
This research aimed to analyze how the event of 7 October 2023 is depicted in the anime Fullmetal Alchemist 2003 and Fullmetal Alchemist: Brotherhood. The theory used in this research was mainly by Julia Kristeva about intertextuality and interdiscursivity. The data used in this paper were taken from an anime called Fullmetal Alchemist 2003 and Brotherhood. This anime was chosen because of its similarity with the event happening in Palestine on 7 October 2023. Its fame has only been rewritten a few months before 2024 after the coming of a new anime entitled Sousou no Frieren. This high ranking from thousands of different anime implies that this anime is very well known among anime watchers. It can be inferred that Ishvalan is more attached and related to Palestine, as tragedy and agony happened in Ishval. It is an empathy that encourages people to support Palestinians.